Trigger urban and regional planning to cope with seismic risks: management, evaluation and mitigation - La Greca, Paolo (TeMA - Journal of Land Use, Mobility and Environment, 2022)
This article - published in Italian in 1995 with the title “Verso un progetto mirato all’organizzazione e alla gestione di un piano di mitigazione dei rischi sismici” in E.D.Sanfilippo e P. La Greca (eds) Piano e Progetto nelle aree a rischio sismico/Planning and design in seismic risk areas, Gangheri Editore, ISBN 88-7448-520-4, Roma – is published again in this new section of TeMA Journal, Evergreen, in its literal English translation. This section aims at drawing the attention of the international scientific community to papers that, despite the passing of time, still present elements of significative scientific interest – insights, anticipations and reflections – enough to deserve careful read back. Abstract Earthquakes account for the most relevant natural risks with a high index of unpredictability that afflict many countries in the world, in many of which the level of development and socio-economic conditions do not allow an adequate response to the effects caused by catastrophes. The unsuitability of public structures and the lack of awareness and consciousness within public opinion towards seismic risk, which is already severely disregarded in industrialised countries, is accentuated in developing countries where populations are daily harassed by the struggle to satisfy the most basic needs.